2020
DOI: 10.1186/s10194-020-01124-3
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of primary headache disorder on quality of life among school students in Kuwait

Abstract: Background: Primary headache disorders have being increasingly reported in younger populations. They can have significant effects on their quality of life and academic achievement and may cause significant distress to their families. Aims and objectives: To assess the burden of primary headache disorder and its impact on the quality of life on school student in Kuwait. Methods: A cross-sectional study was conducted among Kuwaiti primary and middle school students of both genders in randomly selected schools lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…A study indicated that alcohol consumption, smoking, and neck pain are the primary risk factors of migraine in adults. 39 Thus, adults should adopt a healthy lifestyle. Moreover, the incidence rates in elder people are surprisingly much higher in China than in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…A study indicated that alcohol consumption, smoking, and neck pain are the primary risk factors of migraine in adults. 39 Thus, adults should adopt a healthy lifestyle. Moreover, the incidence rates in elder people are surprisingly much higher in China than in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Both descending and ascending hypothalamic fibers, periaqueductal grey, locus coeruleus and nucleus raphe Magnus onto the trigeminal nucleus caudalis can control pain. Spreading cortical depression, which was previously pondered exclusively take place in migraines with aura, now appears to be present in all migraines (8). Central pain pathways are triggered by persistent nociceptive activation of the pericranial my fascia, which can be the cause of chronic tension-type headache conversion (9).…”
Section: Primary Headache's Neurochemistrymentioning
confidence: 98%
“…Compared with the 10-14 age group, migraine in the 20-44 age group can manifest in ways that are markedly different. Study has indicated that factors that become insignificant with age are consumption alcohol, smoking and neck pain [34]. However, the frequency of variables such as stress as a trigger, pressure, stabbing, and throbbing increases during migraine [35].…”
Section: Age-period-cohort Analysismentioning
confidence: 99%